Corneal nonmyelinating Schwann cells illuminated by single‐cell transcriptomics and visualized by protein biomarkers. Issue 3 (16th November 2020) - Bargagna‐Mohan, Paola; Schultz, Gwendolyn; Rheaume, Bruce; Trakhtenberg, Ephraim F.; Robson, Paul; Pal‐Ghosh, Sonali; Stepp, Mary Ann; Given, Katherine S.; Macklin, Wendy B.; Mohan, Royce
Abstract: The cornea is the most innervated tissue in the human body. Myelinated axons upon inserting into the peripheral corneal stroma lose their myelin sheaths and continue into the central cornea wrapped by only nonmyelinating corneal Schwann cells (nm‐cSCs). This anatomical organization is believed to be important for central vision. Here we employed single‐cell RNA sequencing (scRNA‐seq), microscopy, and transgenics to characterize these nm‐cSCs of the central cornea. Using principal component analysis, uniform manifold approximation and projection, and unsupervised hierarchal cell clustering of scRNA‐seq data derived from central corneal cells of male rabbits, we successfully identified several clusters representing different corneal cell types, including a unique cell cluster representing nm‐cSCs. To confirm protein expression of cSC genes, we performed cross‐species validation, employing corneal whole‐mount immunostaining with confocal microscopy in mouse corneas. The expression of several representative proteins of nm‐cSCs were validated. As the proteolipid protein 1 (PLP1) gene was also expressed in nm‐cSCs, we explored the Plp1 ‐eGFP transgenic reporter mouse line to visualize cSCs. Specific and efficient eGFP expression was observed in cSCs in adult mice of different ages. Of several putative cornea‐specific SC genes identified, Dickkopf‐related protein 1 was shown to be present in nm‐cSCs. Taken together, our findings, for the first time, identify important insights and tools toward the study nm‐cSCs in isolated tissue and adult animals. We expect that our results will advance the future study of nm‐cSCs in applications of nerve repair, and provide a resource for the study of corneal sensory function. Abstract : Illumination of nonmyelinating corneal Schwann cells (nm‐cSCs) of the transparent and avascular cornea. (a) Outline of experimental procedures for the endothelial cell‐depleted central corneal cell preparation for scRNA‐seq analysis from rabbit. (b) Major corneal cell populations were identified by unsupervised clustering, with the nm‐cSCs being represented by the purple colored dots. Each dot represents a single cell that was designated by color of the cluster. Dickkopf‐related protein 1 (DKK1) is one of the novel cornea‐specific SC targets identified and cross‐species validated in mouse corneas. The proteolipid protein 1 promoter‐enhanced green fluorescent protein (Plp1‐eGFP) reporter mouse cornea was immunostained for DKK1 ( red ), revealing its co‐localization with eGFP ( green ) reporter expression in SCs. (c) The image on the left shows a cartoon representation of the cornea corresponding to the immunostained images (panels on the right) from the central cornea ( dotted circle, top panel) and limbal/peripheral area ( dotted rectangle, bottom panel ). Detailed magnified views reveal DKK1‐positive staining in nm‐cSCs of the central cornea, as well as myelinated SCs of the peripheral cornea. Scale bars, 10 µm.